Iklim Komunikasi Organisasi Dan Kinerja Pegawai (Hubungan Iklim Komunikasi Organisasi Dengan Kinerja Pegawai di Kecamatan Geyer Kabupaten Grobgan) - Rifanza, Aditya Okky, Agus Triyono, S.Sos, M.Si (2016)
Organizational Communications Climate Relation with the Officer Performance in Subdistrict of Geyer of Regency Grobogan, Skripsi Program Ilmu Komunikasi, Fakultas Komunikasi dan Informatika, Universitas Muhammadiyah Surakarta, 2015. Organizational climate is something that is real that is often felt by a group of people who are in an organization. And what is perceived can affect the behavior of someone who finally can get to determine the level of productivity of a job. An employee's performance is closely related to existing structures, namely the division of labor according the respective sections, the responsibility of an employee on his job either individually or as a group, or organizational, communication has been created by a boss to his subordinates, the award to the source human resources, rewards and sanctions that have been applied. The purpose of this study is to determine the relationship between organizational communication climate to employee performance at the district office Geyer Grobogan. The research results of correlation of 0.697 indicates that there is a link organizational communication climate with employee performance Geyer Subdistrict Grobogan. Because the count r the result is greater than the r in the table so that the relationship between organizational communication climate with the performance of employees in the District Grobogan Geyer are in the strong category. From the result of calculation of 0.697 then according to the interpretation of the above clearly shows the existence of a correlation is between .60 to .79